2019
DOI: 10.3390/biom9070257
|View full text |Cite
|
Sign up to set email alerts
|

Betulinic Acid Suppresses Ovarian Cancer Cell Proliferation through Induction of Apoptosis

Abstract: Ovarian cancer is one of the leading causes of cancer deaths worldwide in women, and the most malignant cancer among the different gynecological cancers. In this study, we explored potentially anticancer compounds from Cornus walteri (Cornaceae), the MeOH extract of which has been reported to show considerable cytotoxicity against several cancer cell lines. Phytochemical investigations of the MeOH extract of the stem and stem bark of C. walteri by extensive application of chromatographic techniques resulted in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 53 publications
1
26
0
1
Order By: Relevance
“…[24][25][26] Furthermore, BA has shown tumorigenesis inhibition in many kinds of cancers, including lung, colon, breast, prostate and pancreatic cancer. [27][28][29][30] In the present study, our results showed that BA distinctly triggered apoptosis and suppressed the proliferation, migration and invasion of GC cells in vitro. The in vivo anti-tumour efficacy was consistent with that reported in vitro studies.…”
Section: Introductionsupporting
confidence: 64%
See 1 more Smart Citation
“…[24][25][26] Furthermore, BA has shown tumorigenesis inhibition in many kinds of cancers, including lung, colon, breast, prostate and pancreatic cancer. [27][28][29][30] In the present study, our results showed that BA distinctly triggered apoptosis and suppressed the proliferation, migration and invasion of GC cells in vitro. The in vivo anti-tumour efficacy was consistent with that reported in vitro studies.…”
Section: Introductionsupporting
confidence: 64%
“…32 It is widely reported that BA is cytotoxic to various types of human cancer cells. [28][29][30] In the present study, we assessed the antitumour effect of BA on human GC cells in vitro and in vivo. nalling pathway and inhibits hepatocellular carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Plants 2021, 10, 431 2 of 8 acid on A2780 human ovarian cancer cells and the renoprotective effect of benzyl salicylate on cisplatin-induced damage in LLC-PK1 kidney proximal tubule cells have been explored and evaluated in our previous studies [16,17]. In the present study, we focused on (-)-leucophyllone, a tirucallane triterpenoid isolated from the further phytochemical investigation of the MeOH extract from C. walteri.…”
Section: Isolation and Identification Of (-)-Leucophyllone From C Wamentioning
confidence: 99%
“…Our previous phytochemical analysis on C. walteri led to the isolation of triterpenoids, including betulinic acid methyl ester, lupenone, lupeol, betulinic acid, methyl 3-O-acetyl betulinate, and sterols such as 6β-hydroxysitostenone, 5α-stigmast-3,6-dione, sitostenone, 3β-sitostanol, and 6α-hydroxy-β-sitostenone [16,17]. Among them, the anticancer effect of betulinic acid on A2780 human ovarian cancer cells and the renoprotective effect of benzyl Plants 2021, 10, 431 2 of 7 salicylate on cisplatin-induced damage in LLC-PK1 kidney proximal tubule cells have been explored and evaluated in our previous studies [16,17]. In the present study, we focused on (-)-leucophyllone, a tirucallane triterpenoid isolated from the further phytochemical investigation of the MeOH extract from C. walteri.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous chemical investigation of C. walteri , we identified triterpenoids and δ-valerolactones, which showed cytotoxicity against several human cancer cell lines, using bioassay-guided fractionation of the methanol extract of C. walteri [ 16 , 17 , 18 , 19 ]. In particular, we found that betulinic acid, a triterpenoid, reduced the viability of A2780 human ovarian carcinoma cells and induced apoptotic cell death through both extrinsic and intrinsic apoptosis pathway [ 19 ]. Furthermore, we identified new tirucallane triterpenoids (cornusalterins N-P) in C. walteri , along with bioactive tirucallane triterpenoids that control adipocyte and osteoblast differentiation [ 20 ].…”
Section: Introductionmentioning
confidence: 99%